213k views
2 votes
Divide -6.2x10^-4 by 9.75x10^6. Express your answer in scientific notation. Round the coefficient to two decimal places.

User Ptownbro
by
4.6k points

2 Answers

6 votes


\\ \rm\hookrightarrow (-6.2* 10^(-4))/(9.75* 10^6)


\\ \rm\hookrightarrow 0.636* 10^(-4-6)


\\ \rm\hookrightarrow 0.636* 10^(-10)


\\ \rm\hookrightarrow 6.4* 10^(-11)

User Abhishek Gangwar
by
5.1k points
9 votes

Answer:


-6.36 * 10^(-11)

Explanation:


(-6.2*10^(-4))/(9.75*10^6)


\implies (-6.2)/(9.75)* (10^(-4))/(10^6)


\implies (-6.2)/(9.75)=-6.36*10^(-1)

Apply exponent rule:
(a^b)/(a^c)=a^(b-c)


\implies (10^(-4))/(10^6)=10^((-4-6))=10^(-10)


\implies (-6.2)/(9.75)* (10^(-4))/(10^6)=-6.36 * 10^(-1) * 10^(-10)

Apply exponent rule:
a^b * a^c=a^((b+c))


\implies -6.36 * 10^(-1) * 10^(-10)=-6.36 * 10^((-1-10))


\implies -6.36 * 10^(-11)

User Matanox
by
4.9k points